Establishment of Sensory Wheel and Quantitative Descriptive Profile for Pixian Douban - CHEN Houyin, ZHONG Kui, YUN Zhenyu, SHI Bolin, WANG Houyin, ZHANG Yao, ZHANG Lihan, HE Xiaoning, XIANG Yake, ZHAO Lei (Shipin Kexue)
In order to explore the sensory characteristics of Pixian Douban (PXDB), a Chinese geographical indication product, a trained sensory panel was used to establish a sensory wheel and a quantitative descriptive profile (QDP) for PXDB. The pivot profile method and the M-value were combined to develop 53 sensory descriptors in terms of appearance, basic taste, aroma, flavor and texture for 21 commercial PXDB products. Out of these 53 sensory descriptors, 23 were further selected and an intensity reference sample was developed for each of them. Quantitative descriptive analysis (QDA) was used to evaluate the sensory quality of different types and grades of PXDB. The results showed that traditional PXDB had stronger soy sauce-like and spicy flavor, a stickier texture, more complete broad beans, and greater hardness. Compared with traditional PXDB, chili oil PXDB, reddish brown in color, had stronger oily and spicy aromas, wettability, and oily flavor. Higher grades of PXDB had more prominent soy sauce-like aroma and fermented soybean-like flavor and tasted more mellow. This study provides basic data and a reference for the sensory quality evaluation, quality control and improvement of PXDB.